Emerging fungal pathogen Ophidiomyces ophiodiicola in wild European snakes - Franklinos, Lydia H V; Lorch, Jeffrey M; Bohuski, Elizabeth; Rodriguez-Ramos Fernandez, Julia; Wright, Owen N; Fitzpatrick, Liam; Petrovan, Silviu; Durrant, Chris; Linton, Chris; Baláž, Vojtech; Cunningham, Andrew A; Lawson, Becki (Scientific reports, 2017)
Snake fungal disease (SFD) is an emerging disease of conservation concern in eastern North America. Ophidiomyces ophiodiicola, the causative agent of SFD, has been isolated from over 30 species of wild snakes from six families in North America. Whilst O. ophiodiicola has been isolated from captive snakes outside North America, the pathogen has not been reported from wild snakes elsewhere. We screened 33 carcasses and 303 moulted skins from wild snakes collected from 2010-2016 in Great Britain and the Czech Republic for the presence of macroscopic skin lesions and O. ophiodiicola. The fungus was detected using real-time PCR in 26 (8.6%) specimens across the period of collection. Follow up culture and histopathologic analyses confirmed that both O. ophiodiicola and SFD occur in wild European snakes. Although skin lesions were mild in most cases, in some snakes they were severe and were considered likely to have contributed to mortality. Culture characterisations demonstrated that European isolates grew more slowly than those from the United States, and phylogenetic analyses indicated that isolates from European wild snakes reside in a clade distinct from the North American isolates examined. These genetic and phenotypic differences indicate that the European isolates represent novel strains of O. ophiodiicola. Further work is required to understand the individual and population level impact of this pathogen in Europe.
Keywords: Animal Diseases; Ascomycota; Genes, Fungal; Animals; North America; Snakes; Phylogeny; nemoci zvířat; zvířata; fylogeneze; Severní Amerika; hadi; geny hub